THE INFLUENCE OF DEMOCRATIC PARENTING PATTERNS AND SELF-REGULATED LEARNING ON THE ADJUSTMENT OF NEW STUDENTS AT THE DARULARAFAH RAYA ISLAMIC BOARDING SCHOOL MEDAN - Wardani, Ika Sri; Nuraini, Nuraini; Dewi, Salamiah Sari (Research and Development Journal of Education, 2025)
This study aims to determine the effect of democratic parenting patterns and self-regulated learning on self-adjustment of class X students in one of the Islamic boarding schools in Medan City. This study uses a quantitative method using a total sampling technique involving 150 students. The research instruments used in this study were the democratic parenting pattern scale, the self-regulated learning scale and the self-adjustment scale. Data were analyzed using the Structural Equation Model (SEM) method through the Smart PLS 4.0 and SPSS 26.0 programs. The results showed that democratic parenting patterns had a positive and significant effect on self-adjustment with a coefficient value of 0.524 and a P-Value = 0.000 < 0.05. Self-regulated learning has a positive and significant effect on self-adjustment with a coefficient value of 0.500 and P-Values = 0.000 < 0.05. Democratic Parenting Patterns and Self-Regulated Learning are able to explain or influence Self-Adjustment by 66.8%. This shows that both factors play an important role in the psychological development of children and adolescents. The remaining 33.2% is influenced by other factors.